2010
DOI: 10.1007/s00508-010-1336-y
|View full text |Cite
|
Sign up to set email alerts
|

Explanatory model of prescribing behavior in prescription of statins in family practice

Abstract: The determinants that influence statin prescribing behavior among GPs in our study covered an array of explanatory items consistent with proposals in the literature but factors differ to some extent from proposed theoretical models. The explanatory model explained a high proportion of the variation in deciding on a particular statin. Efficacy and safety remain important factors in selection of an appropriate drug but are far from being the most or only important factors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(14 citation statements)
references
References 23 publications
1
13
0
Order By: Relevance
“…The associations between the variables were found to be lower than the results of Cronbach’s alpha, indicating evidence of the discriminant validity of the measure. This finding maybe not surprising, considering previous research findings confirmed that drug requests by brand name and patient expectations are found to have a positive effect on the physician prescriptions 13,70…”
Section: Discussionsupporting
confidence: 65%
See 3 more Smart Citations
“…The associations between the variables were found to be lower than the results of Cronbach’s alpha, indicating evidence of the discriminant validity of the measure. This finding maybe not surprising, considering previous research findings confirmed that drug requests by brand name and patient expectations are found to have a positive effect on the physician prescriptions 13,70…”
Section: Discussionsupporting
confidence: 65%
“…The results found that drug characteristics have no significant relationship with prescribing decisions. Perhaps that the characteristics of the drug make it entail diverse viewpoints of the products in the prescription of drugs 13,71. This argument corresponds to Pinto et al , who opine that elements such as side effects and cost were considered less relevant by the physicians 72.…”
Section: Discussionmentioning
confidence: 93%
See 2 more Smart Citations
“…Whilst physicians emphasize clinical efficacy, they seem willing to take cost under certain conditions [2]. The benefits of the drug were found to be a distinct factor influencing prescription [52]. In developing countries, the consumption of drugs is largely linked to the purchasing power of the patient [2].…”
Section: Moderating Effects Of Benefit-cost Profile Of Drugsmentioning
confidence: 99%